Experiences on Establishment of Scots Pine (Pinus sylvestris L.) Plantation in Ash Dump Sites of Reftinskaya Power Plant, Russia - Zalesov, S. V.; Ayan, S.; Zalesova, E. S.; Opletaev, A. S. (Kastamonu Univ, 2020)
Since the middle of the last century in the Urals of Russia there has been a problem of environmental pollution by man-made emissions. The purpose of this investigation has been to summarize the recultivation experience of Reftinskaya power plant ash dump. The station was put into operation in 1970 and it is the largest one in Russia. Specific feature of the used coal is high content of ash (47%). Daily consumption of coal in winter period constitutes 48 thousand tons. Yearly emissions of the station constitute 400 thousand tons. The main components of the emissions are sulphureous anhydride (up to 40%) solid stuff (up to 50%) and nitric oxides. The Scots pine (Pinus sylvestris L.) plantations on ash dumps have shown good adaptation and growth. The plantations have formed 143 m(3)/ha total volume at the age of 20 in 1st site index of the recultivation site of the ash dump with ash layer up to 7 m. Weakly alkaline reaction of the ash spread by wind promoted soil dioxidation that results in soil fertility increasing significantly on territory of adjacent stands. Recultivation process includes two main stages which are ash dump surface covering with 25-40 cm soil layer, planting with 2-year old Scots pine (Pinus sylvestris L.) seedling.
Keywords: DISTURBED LAND; ASH DUMP; THERMAL ELECTRIC STATION; RECULTIVATION; PINUS SYLVESTRIS; 13. Climate action; 7. Clean energy; 6. Clean water